Evaluation of neoadjuvant immunotherapy and traditional neoadjuvant therapy for resectable esophageal cancer: a systematic review and single-arm and network meta-analysis - Wang, Hesong; Song, Chunyang; Zhao, Xiaohan; Deng, Wenzhao; Dong, Jing; Shen, Wenbin (Frontiers in Immunology, 2023)
Objective This systematic review and meta-analysis aimed to investigate the role of neoadjuvant immunochemotherapy with or without radiotherapy [NIC(R)T] compared to traditional neoadjuvant therapies, without immunotherapy [NC(R)T]. Summary background data NCRT followed by surgical resection is recommended for patients with early-stage esophageal cancer. However, it is uncertain whether adding immunotherapy to preoperative neoadjuvant therapy would improve patient outcomes when radical surgery is performed following neoadjuvant therapy. Methods We searched PubMed, Web of Science, Embase, and Cochrane Central databases, as well as international conference abstracts. Outcomes included R0, pathological complete response (pCR), major pathological response (mPR), overall survival (OS) and disease-free survival (DFS) rates. Results We included data from 5,034 patients from 86 studies published between 2019 and 2022. We found no significant differences between NICRT and NCRT in pCR or mPR rates. Both were better than NICT, with NCT showing the lowest response rate. Neoadjuvant immunotherapy has a significant advantage over traditional neoadjuvant therapy in terms of 1-year OS and DFS, with NICT having better outcomes than any of the other three treatments. There were no significant differences among the four neoadjuvant treatments in terms of R0 rates. Conclusions Among the four neoadjuvant treatment modalities, NICRT and NCRT had the highest pCR and mPR rates. There were no significant differences in the R0 rates among the four treatments. Adding immunotherapy to neoadjuvant therapy improved 1-year OS and DFS, with NICT having the highest rates compared to the other three modalities. Systematic Review Registration https://inplasy.com/inplasy-2022-12-0060/, identifier INPLASY2022120060.